Biocontrol of Listeria monocytogenes and Salmonella Typhimurium in hydroponics: Evaluating the efficacy of plant growth promoting bioinoculants - Grace Akumu; Leslie D. Thompson; Mindy M. Brashears; Catherine R. Simpson; Christopher J. Currey; Angela M. Walla (Food Control, 2026)

Fire–Moisture Interactions Shape Recovery Trajectories Across Temperate Vegetation Communities - Emily K. Simpson; Glenda M. Wardle; Christopher R. Dickman; Aaron C. Greenville (Global Change Biology, 2026)
The recovery of vegetation following fire is increasingly shaped by concurrent climate‐driven hydrological extremes, such as drought and extreme precipitation. Under these multi‐disturbance scenarios vegetation communities are likely to show different recovery thresholds and trajectories of change, but this is yet to be fully understood or quantified. We used the Greater Blue Mountains World Heritage Area in south‐eastern Australia as a model system to assess how sustained moisture surplus or deficit could differentially influence the recovery of forest, heath and wetland vegetation from low‐extreme severity fire. From 2015 to 2024, this region experienced severe drought, extensive bushfires (the ‘Black Summer’ bushfires) and extreme rainfall events. By using a new remote‐sensing index (the Post‐fire Stability Index) that measures the rate of change in a disturbed system, we found that most vegetation communities could recover following low‐severity fire even in the case of poor soil moisture conditions, but moisture became increasingly limiting as burn severity increased. Certain communities, such as wet sclerophyll forests and freshwater wetlands, experienced disproportionate declines (up to times greater than other communities) as burn severity and drought intensified. These communities are likely at greatest risk as climate drying escalates. We stress that future recovery from fire in temperate communities will be governed not only by the characteristics of the fire itself and those of the affected vegetation community, but also by the extent to which these characteristics interact with prevailing hydro‐climatic conditions.

When everything is violence, nothing is violence: Response to Koot et al. (2025) - Fergus O'Leary Simpson; Lorenzo Pellegrini; Olajide Akinleye‐Martins; Leif Brottem; Elie Lunanga; Christopher Day; Elias Maombi Ndatabaye; Lara Collart; Naziru Zakari Muhammad; Marijke Verpoorten; Helen Kopnina; Richard Sufo (Conservation Biology, 2026)

The closer, the better: intratumoral delivery of a thermoresponsive gemcitabine-loaded hydrogel in preclinical PDAC models - Andrea Vallés-Martí; Ajinkya Manelkar; Christopher R. Simpson; Priscilla Kinderman; Eveline de Jonge-Muller; Anthea van der Wielen; Stefanus G.T. Janson; Ahmad Alrawahneh; Li Zihao; Tushar Tomar; Mike G.W. de Leeuw; Helena M. Kelly; et al. (Drug Delivery and Translational Research, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Assessing the potential impact of environmental land management schemes on emergent infectious disease risks - Christopher J. Banks; Katherine Simpson; Nick Hanley; Rowland R. Kao (Journal of Environmental Management, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Circular economy and the Titanic effect: Analysis of 145 case studies - Miranda Braga Gomes Nogueira; Jeanette Simpson; Adam Christopher Snow; Fiona Charnley; Begüm Yontar Avcı; Kevin Brown; Tanvir Ahmed (Sustainable Production and Consumption, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The repeatability of a cycling exercise-heat stress test in a male population - Jake Shaw; E. Cole; Andrew J. Simpson; Christopher J. Tyler; Andrew T. Garrett (Journal of Thermal Biology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Testing in-situ apatite Lu–Hf dating in polymetamorphic mafic rocks: a case study from Palaeoproterozoic southern Australia - Dillon A. Brown; Anthony Reid; Elizabeth A. Jagodzinski; Megan Williams; Alex Simpson; Mark Pawley; Christopher L. Kirkland; Claire Wade; Alexander T. De Vries Van Leeuwen; Stijn Glorie (Contributions to Mineralogy and Petrology, 2024)
In mafic systems where primary mineral assemblages have witnessed moderate- to high-temperature hydrous overprinting and deformation, little is known about the retentivity of the Lu–Hf isotopic system in apatite. This study presents apatite laser-ablation Lu–Hf and U–Pb geochronology, zircon geochronology, and detailed petrological information from polymetamorphic mafic intrusions located in the central-western Gawler Craton in southern Australia, which records an extensive tectonometamorphic history spanning the Neoarchaean to the Mesoproterozoic. Zircon records magmatic crystallisation ages of c. 2479–2467 Ma, coinciding with the onset of the c. 2475–2410 Ma granulite-facies Sleafordian Orogeny. The amphibole-dominant hydrous assemblages which extensively overprint the primary magmatic assemblages are hypothesised to post-date the Sleafordian Orogeny. The Lu–Hf and U–Pb isotopic systems in apatite are used to test this hypothesis, with both isotopic systems recording significantly younger ages correlating with the c. 1730–1690 Ma Kimban Orogeny and the c. 1590–1575 Ma Hiltaba magmatic event, respectively. While the early Mesoproterozoic apatite U–Pb ages are attributed to thermal re-equilibration, the older Lu–Hf ages are interpreted to reflect re-equilibration facilitated primarily by dissolution-reprecipitation, but also thermally activated volume diffusion. The mechanisms of Lu–Hf isotopic resetting are distinguished based on microscale textures and trace element abundances in apatite and the integration of apatite-amphibole textural relationships and temperatures determined from the Ti content in amphibole. More broadly, the results indicate that at low to moderate temperatures, apatite hosted in mafic rocks is susceptible to complete recrystallisation in rocks that have weak to moderate foliations. In contrast, at higher temperatures in the absence of strain, the Lu–Hf system in apatite is comparatively robust. Ultimately, the findings from this study advance our understanding of the complex role that both metamorphism and deformation play on the ability of mafic-hosted apatite to retain primary Lu–Hf isotopic signatures.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Evaluation of Orthotrichum lyellii moss as a biomonitor of diesel exhaust - Christopher Zuidema; Michael Paulsen; Christopher D. Simpson; Sarah E. Jovan (Science of The Total Environment, 2024)

Acoustic backscattering at a tidal intrusion front - Christopher Bassett; Andone C. Lavery; David Ralston; W. Rockwell Geyer; Joseph T. Jurisa; Jim Thomson; David A. Honegger; Alexandra Simpson; Malcom E. Scully; Merrick C. Haller (Progress in Oceanography, 2023)

Apatite laser ablation Lu Hf geochronology: A new tool to date mafic rocks - Melissa B.K. Kharkongor; Stijn Glorie; Jacob Mulder; Christopher L. Kirkland; David Chew; Barry Kohn; Alexander Simpson (Chemical Geology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Improving the representation of groundwater processes in a large-scale water resources model - Helen Elizabeth Baron; Virginie D. J. Keller; R. Horan; Donald John MacAllister; Mike Simpson; Christopher R. Jackson; Helen A. Houghton-Carr; Nathan Rickards; Kaushal K. Garg; Muddu Sekhar; Alan MacDonald; Gwyn Rees (Hydrological Sciences Journal, 2023)

Role of Indigenous and local knowledge in seasonal forecasts and climate adaptation: A case study of smallholder farmers in Chiredzi, Zimbabwe - Luckson Zvobgo; Peter Johnston; Oladapo M. Olagbegi; Nicholas P. Simpson; Christopher H. Trisos (Environmental Science & Policy, 2023)

One step antimicrobial coatings for medical device applications based on low fouling polymers containing selenium nanoparticles - Fanyi Li; Tao Huang; Paul Pasic; Christopher D. Easton; Nicolas H. Voelcker; Daniel E. Heath; Neil M. O'Brien-Simpson; Andrea J. O'Connor; Helmut Thissen (Chemical Engineering Journal, 2023)

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Funding flows for climate change research on Africa: where do they come from and where do they go? - Indra Overland; Haakon Fossum Sagbakken; Aidai Isataeva; Galina Kolodzinskaia; Nicholas Philip Simpson; Christopher Trisos; Roman Vakulchuk (Climate and Development, 2022)

Webinar and survey on quality management principles within the Australian and New Zealand ACPSEM Workforce - Emily Simpson-Page; Paul Coogan; Tomas Kron; Nicholas Lowther; Rebecca Murray; Christopher Noble; Ian Smith; Rachael Wilks; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2022)

The role of indigenous knowledge and local knowledge in water sector adaptation to climate change in Africa: a structured assessment - Luckson Zvobgo; Peter Johnston; Portia Adade Williams; Christopher H. Trisos; Nicholas P. Simpson (Sustainability Science, 2022)
Evidence is increasing of human responses to the impacts of climate change in Africa. However, understanding of the effectiveness of these responses for adaptation to climate change across the diversity of African contexts is still limited. Despite high reliance on indigenous knowledge (IK) and local knowledge (LK) for climate adaptation by African communities, potential of IK and LK to contribute to adaptation through reducing climate risk or supporting transformative adaptation responses is yet to be established. Here, we assess the influence of IK and LK for the implementation of water sector adaptation responses in Africa to better understand the relationship between responses to climate change and indigenous and local knowledge systems. Eighteen (18) water adaptation response types were identified from the academic literature through the Global Adaptation Mapping Initiative (GAMI) and intended nationally determined contributions (iNDCs) for selected African countries. Southern, West, and East Africa show relatively high evidence of the influence of IK and LK on the implementation of water adaptation responses, while North and Central Africa show lower evidence. At country level, Zimbabwe displays the highest evidence (77.8%) followed by Ghana (53.6%), Kenya (46.2%), and South Africa (31.3%). Irrigation, rainwater harvesting, water conservation, and ecosystem-based measures, mainly agroforestry, were the most implemented measures across Africa. These were mainly household and individual measures influenced by local and indigenous knowledge. Adaptation responses with IK and LK influence recorded higher evidence of risk reduction compared to responses without IK and LK. Analysis of iNDCs shows the most implemented water adaptation actions in academic literature are consistent with water sector adaptation targets set by most African governments. Yet only 10.4% of the African governments included IK and LK in adaptation planning in the iNDCs. This study recommends a coordinated approach to adaptation that integrates multiple knowledge sources, including IK and LK, to ensure sustainability of both current and potential water adaptation measures in Africa.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Development of Redwood Regeneration after Conifer Partial Harvest and Hardwood Management - John-Pascal Berrill; Lynn A Webb; Kristy L DeYoung; Christa M Dagley; Christopher G Bodle; Sean M Simpson (Forest Science, 2021)
Harvesting of commercial conifer species from conifer-hardwood mixtures can leave residual stands dominated by hardwoods. Removing unwanted hardwoods by cutting or herbicide makes growing space available to residual trees and regeneration and can restore conifer dominance. Forest managers of north coastal California need guidance on how such treatments affect subsequent growth of planted redwoods (Sequoia sempervirens [D. Don.] Endl.) or natural regeneration, as well as proliferation of undesirable species. Our observational study reconstructed growth of 108 regenerating redwoods in 26 treated stands. Residual stand density was the main driver of height and diameter growth in the new cohort of redwoods, irrespective of whether hardwoods were cut or received herbicide frill treatment (prevents resprouting). At lower residual stand densities, there were higher densities of natural regeneration (ingrowth) of conifers and hardwoods, which affected diameter at breast height (dbh) growth of regenerating redwoods. After heavier cutting of hardwoods, this ingrowth comprised a greater proportion of unwanted hardwood regeneration. Therefore, frill treatment is recommended when the objective of management is to reduce hardwood stocking and regeneration. Combining partial harvesting of conifers with cutting or frill treatment of hardwood is another option that reduces stand density to promote height and dbh growth of regenerating redwoods.

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Cetuximab Exhibits Sex Differences in Lymphatic Exposure after Intravenous Administration in Rats in the Absence of Differences in Plasma Exposure - Esther Kuilamu; Christopher Subasic; Gary J Cowin; Fiona Simpson; Rodney F Minchin; Lisa M Kaminskas (Pharmaceutical Research, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Iowa Stream Nitrate, Discharge and Precipitation: 30-Year Perspective - Christopher S. Jones; Keith E. Schilling; Ian M. Simpson; Calvin F. Wolter (Environmental Management, 2018)

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

Parkinsonism Signs and Symptoms in Agricultural Pesticide Handlers in Washington State - Susan Searles Nielsen; Shu-Ching Hu; Harvey Checkoway; Maria Negrete; Pablo Palmández; Theresa Bordianu; Brad A. Racette; Christopher D. Simpson (Journal of Agromedicine, 2017)

Assessment of Damage and Adaptation Strategies for Structures and Infrastructure from Storm Surge and Sea Level Rise for a Coastal Community in Rhode Island, United States - Christopher Small; Tyler Blanpied; Alicia Kauffman; Conor O’Neil; Nicholas Proulx; Mathew Rajacich; Hailey Simpson; Jeffrey White; Malcolm Spaulding; Christopher Baxter; J. Swanson (Journal of Marine Science and Engineering, 2016)
This paper presents an evaluation of inundation, erosion, and wave damage for a coastal community in Rhode Island, USA. A methodology called the Coastal Environmental Risk Index (CERI) was used that incorporates levels of inundation including sea level rise, wave heights using STWAVE, and detailed information about individual structures from an E911 database. This information was input into damage functions developed by the U.S. Army Corps of Engineers following Hurricane Sandy. Damage from erosion was evaluated separately from local published erosion rates. Using CERI, two different adaptation strategies were evaluated that included a combination of dune restoration, protective berms, and a tide gate. A total of 151 out of 708 structures were estimated to be protected from inundation and wave action by the combined measures. More importantly, the use of CERI allowed for the assessment of the impact of different adaptation strategies on both individual structures and an entire community in a Geographical Information Systems (GIS) environment. This tool shows promise for use by coastal managers to assess damage and mitigate risk to coastal communities.

Using exposure windows to explore an elusive biomarker: blood manganese - Marissa G. Baker; Bert Stover; Christopher D. Simpson; Lianne Sheppard; Noah S. Seixas (International Archives of Occupational and Environmental Health, 2016)

The fate of fertiliser P in soil under pasture and uptake by subterraneum clover – a field study using 33P-labelled single superphosphate - Timothy I. McLaren; Michael J. McLaughlin; Therese M. McBeath; Richard J. Simpson; Ronald J. Smernik; Christopher N. Guppy; Alan E. Richardson (Plant and Soil, 2016)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

A reference typology of low alkalinity lakes in the UK based on pre-acidification diatom assemblages from lake sediment cores - Richard W. Battarbee; Gavin L. Simpson; Helen Bennion; Christopher Curtis (Journal of Paleolimnology, 2011)

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Melanoma invasion in reconstructed human skin is influenced by skin cells – investigation of the role of proteolytic enzymes - Paula Eves; Efthymia Katerinaki; Claire Simpson; Christopher Layton; Rebecca Dawson; Gareth Evans; Sheila Mac Neil (Clinical & Experimental Metastasis, 2003)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)